2010
DOI: 10.1007/s00228-010-0823-4
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CYP1A2 by heavy coffee consumption is associated with the CYP1A2 −163C>A polymorphism

Abstract: CYP1A2 polymorphism -163C>A has an important increasing effect on CYP1A2 inducibility by heavy coffee consumption and may possibly be a contributing factor for interindividual variations in CYP1A2 enzyme activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 27 publications
1
70
0
3
Order By: Relevance
“…In a subset of the present study cohort, it has previously been shown that moderate to high coffee intake modulates ER status in women with the CYP1A2*1F A/A genotype, but not in those with the CYP1A2*1F C-allele [18]. The CYP1A2 enzyme is more inducible by coffee in CYP1A2*1F A/A carriers [19,20]. It is therefore plausible that tamoxifen response is influenced by the CYP1A2*1F genotype and coffee intake and that any effect of coffee may be dependent on the CYP1A2*1F genotype.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In a subset of the present study cohort, it has previously been shown that moderate to high coffee intake modulates ER status in women with the CYP1A2*1F A/A genotype, but not in those with the CYP1A2*1F C-allele [18]. The CYP1A2 enzyme is more inducible by coffee in CYP1A2*1F A/A carriers [19,20]. It is therefore plausible that tamoxifen response is influenced by the CYP1A2*1F genotype and coffee intake and that any effect of coffee may be dependent on the CYP1A2*1F genotype.…”
Section: Introductionmentioning
confidence: 57%
“…Intake of caffeinated coffee may thus result in increased activation of tamoxifen via CYP1A2 or CYP2C8/9, a hypothesis consistent with our finding of fewer early events in tamoxifen-treated patients with ER+ tumors and moderate to high coffee consumption. Moreover, others have reported that carriers of the CYP1A2*1F A/A genotype but not the CYP1A2*1F C-allele who consume 3+ cups/day have a higher inducibility of CYP1A2 compared to non-consumers [20]. This may explain the finding of an association between low coffee consumption in combination with at least one CYP1A2*IF Callele or CYP2C8*3 allele with an over 3-fold risk for early breast cancer events in tamoxifen-treated patients with ER+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…An A → C polymorphism of the CYP1A2 has been associated with [87,88]. Those with the homozygous A/A allele have been found to metabolise caffeine faster than C allele carriers (A/C and C/C); homozygous C/C individuals have the slowest caffeine metabolism [88][89][90]. A slower caffeine metabolism such as that found in A/C and C/C allele carriers could result in a longer half-life thus prolonging the ergogenic effect of caffeine whereas faster metabolism would result in a faster breakdown of caffeine, reducing the half-life of caffeine in the body.…”
Section: Discussionmentioning
confidence: 99%
“…40 Furthermore, high coffee consumption has been reported to induce CYP1A2 activity, especially in subjects with two rapid alleles (CYP1A2*1A) and this may have influenced our results. 41,42 It is hypothesized that tea consumption may lower CRC risk through its antioxidant components protecting colonic epithelial cells against oxidative radicals. 43,44 Despite the consistently observed protective effect of tea components in animal studies, a protective effect has, in general, not been demonstrated in epidemiological studies, 11,13 and is further confirmed by the present study.…”
Section: Discussionmentioning
confidence: 99%